Rewiring andragogy: the teaching-learning-evaluation (T-L-E) hackathon blueprint - Sophia Gaikwad; Ashwini Wadegaonkar; Fadi K. Dib (Frontiers in Education)
This paper explores how a hackathon-based approach can enhance the application of andragogical principles and how higher education institutions can implement a teacher-focused initiative, the Teaching-Learning-Evaluation (T-L-E) Hackathon, to promote problem-solving, collaboration, and the design of innovative interventions in teaching, learning, and evaluation. Unlike traditional hackathons centered on software development, the T-L-E Hackathon engages educators in collaboratively addressing real-world educational challenges and developing practical instructional solutions. This case study presents the roadmap for planning and executing the hackathon, highlighting its structured process and evaluation criteria. A total of 53 teams comprising 185 faculty members from 10 cities in Maharashtra and 8 other Indian states participated. The T-L-E Hackathon emerged as a systemic tool for educational transformation, integrating teachers’ voices into the broader discourse of educational reform and fostering innovation directly linked to classroom practice.